Introductory Guide to the Common European Framework of Reference (CEFR) for English Language Teachers - Prajapati, Martik (Integrated Journal for Research in Arts and Humanities, 2022)
The Common European Framework of Reference for Languages: Learning, Teaching, Assessment, abbreviated in English as CEFR or CEF or CEFRL, is a guideline used to describe achievements of learners of foreign languages across Europe and, increasingly, in other countries. The CEFR is also intended to make it easier for educational institutions and employers to evaluate the language qualifications of candidates for education admission or employment. Its main aim is to provide a method of learning, teaching, and assessing that applies to all languages in Europe. The Common European Framework of Reference (CEFR) guidelines describe language proficiency of learners on a scale of 6 levels. While the description of CEFR guidelines is generic across languages, the development of automated proficiency classification systems for different languages follows different approaches.